Comparison of Three Nursing Workload Assessment Tools in the Neonatal Intensive Care Unit and Their Association with Outcomes of Very Preterm Infants - Lemieux-Bourque, Charlotte; Piedboeuf, Bruno; Gignac, Simon; Taylor-Ducharme, Sharon; Julien, Anne-Sophie; Beltempo, Marc (American Journal of Perinatology, 2020)
Objective Nursing workload assessment tools are widely used to determine nurse staffing requirements in the neonatal intensive care unit (NICU). We aimed to compare three existing workload assessment tools and assess their association with mortality or morbidity among very preterm infants.Study Design Single-center retrospective cohort study of infants born <33 weeks and admitted to a 52-bed tertiary NICU in 2017 to 2018. Required nurse staffing was estimated for each shift using the Winnipeg Assessment of Neonatal Nursing Needs Tool (WANNNT) used as reference tool, the Quebec Provincial NICU Nursing Ratio (QPNNR), and the Canadian NICU Resource Utilization (CNRU). Poisson regression models with robust error variance estimators were used to assess the association between nursing provision ratios (actual number of nurses/required number of nurses) during the first 7 days of admission and neonatal outcomes.Results Median number of nurses required per shift using the WANNNT was 25.0 (interquartile range [IQR]: 23.1–26.7). Correlation between WANNNT and QPNNR was high (r = 0.92, p < 0.0001), but the QPNNR underestimated the number of nurses per shift by 4.8 (IQR: 4.1–5.4). Correlation between WANNNT and CNRU was moderate (r = 0.45, p < 0.0001). The NICU nursing provision ratios during the first 7 days of admission calculated using the WANNNT (adjusted risk ratio [aRR]: 0.96, 95% confidence interval [CI]: 0.93–0.99) and QPNNR (aRR: 0.97, 95% CI: 0.95–0.99) were associated with mortality or morbidity.Conclusion Lower nursing provision ratio calculated using the WANNNT and CNRU during the first 7 days of admission is associated with an increased risk of mortality/morbidity in very preterm infants.Key Points
Keywords: nurse staffing; health care organization; infant; neonatal intensive care unit